Fatigue in aerostructures—where structural health monitoring can contribute to a complex subject - Boller, Christian; Buderath, Matthias (Philosophical transactions of the Royal Society of London. Series A: Mathematical, physical, and engineering sciences, 2007)
An overview of the aircraft design and maintenance process is given with specific emphasis on the fatigue design as well as the phenomenon of the ageing aircraft observed over the life cycle. The different measures taken to guarantee structural integrity along the maintenance process are addressed. The impact of structural health monitoring as a means of possibly revolutionizing the current aircraft structural monitoring and design process is emphasized and comparison is made to jet engines and helicopters, where health monitoring has already found the respective breakthrough.